Place meaning and the visually impaired: The impact of sound parameters on place attachment and identity - Rizopoulos, Charalampos; Gazi, Angeliki; Christidis, Yiannis (My University, 2014)
This paper outlines some theoretical considerations regarding the concept of place meaning as applied to populations of visually impaired users of mobile location-based applications. The concept of place meaning and its constituent elements, place attachment and place identity, are explored in detail and a research design on place meaning for visually impaired smartphone users is outlined as a first step toward the systematic investigation of the differences in the creation of place attachment and place identity between sighted and visually impaired individuals as a result of auditory stimuli emerging from the urban soundscape.
Keywords: Affect; Location-aware applications; Place meaning; Soundscape